2007
DOI: 10.1111/j.1743-6109.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Activity of the Tunica Albuginea and Corpora Cavernosa: Possible Role of Tunica Albuginea in the Erectile Mechanism

Abstract: Introduction It is claimed that the tunica albuginea (TA) shares in the erectile mechanism by compressing the emissary veins passing through it. However, the TA does not contain smooth muscle fibers. Aim We investigated the hypothesis that TA lacks a contractile activity on the emissary veins passing through it. Methods Fourteen healthy male volunteers (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the gut possesses an electric activity, which is suggested to originate from the smooth muscle fibers and to be responsible for the tonic contraction of the gut [9][10][11][12][13][14][15][16][17]. The smooth muscles have a resting electric activity, which appears to create the smooth muscle tone [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the gut possesses an electric activity, which is suggested to originate from the smooth muscle fibers and to be responsible for the tonic contraction of the gut [9][10][11][12][13][14][15][16][17]. The smooth muscles have a resting electric activity, which appears to create the smooth muscle tone [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that approximately 80% of the men with vasculogenic erectile dysfunction (ED) have evidence of failure to store blood (venous leakage) within the corpora cavernosa [1]. Venogenic ED (VED) may be caused by the formation of large venous channels draining the corpora cavernosa, degenerative changes to the tunica albuginea, structural alterations of the cavernous smooth muscle and endothelium [2–13]. Whatever the cause, the main goal of treatment is to occlude this venous outflow [8–10,14–17].…”
Section: Introductionmentioning
confidence: 99%
“…Venogenic ED (VED) may be caused by the formation of large venous channels draining the corpora cavernosa, degenerative changes to the tunica albuginea, structural alterations of the cavernous smooth muscle and endothelium [2][3][4][5][6][7][8][9][10][11][12][13]. Whatever the cause, the main goal of treatment is to occlude this venous outflow [8][9][10][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%